Aplicação do sandbox na contratação de encomendas tecnológicas nos serviços sociais autônomos SESC e SENAC: análise sobre contratação de inovação tecnológica e gestão de riscos - Rocha, Gustavo Santos Rocha da (Universidade do Vale do Rio dos Sinos, 2025)
This master's thesis investigates how the application of an experimental regulatory environment, or sandbox, can consolidate governance and risk control in the contracting of technological orders, with an emphasis on the advantages and limitations of this innovative model. Increasing digitalization and the relentless pursuit of innovation have compelled organizations in all sectors to explore new regulatory approaches, such as the use of regulatory sandboxes, especially in critical areas such as technology contracting. In the context of the Autonomous Social Services Sesc and Senac, essential institutions in the Brazilian educational and commercial landscape, the implementation of sandboxes may offer a promising way to manage risks and govern the process of technological innovation. The relevance of this experimental model is even more pronounced in the current scenario, where the speed of technological change and the demands of regulatory compliance impose significant challenges for organizations. From this context, the research problem is presented below: How can the application of the sandbox consolidate governance and risk control in the contracting of technological orders for the Social Service of Commerce - Sesc and the National Service for Commercial Apprenticeship - Senac? Regarding the general objective, the study seeks to ascertain the advantages and limitations of the experimental regulatory environment (regulatory sandbox) in the process of contracting technological orders at Sesc and Senac. Five specific objectives were defined for this research: to investigate the impact of the sandbox on compliance with current regulations and legislation during the contracting of innovative technologies; to verify the benefits of the sandbox in creating a controlled space for testing technological orders, with emphasis on the ability to adapt innovations in order to meet the specific needs of Sesc and Senac; to examine the regulatory and legal environment surrounding Sesc and Senac in order to identify the legal limitations, with emphasis on the responsibility of managers with regard to the use of resources in technological innovation and the risks involved; propose a sandbox implementation plan adapted to the context of Sesc and Senac, supported by a set of good practices, as a potentially positive strategy to increase efficiency in the processes associated with contracting technological orders in the autonomous social services Sesc and Senac; analyze the legal parameters for assessing and mitigating contractual risks in the sandbox. To conduct this study, the Narrative Bibliographic Review method, also known as Literature Review, was adopted. This method follows the conceptions of qualitative research and is configured as an exploratory investigation. It was concluded that the implementation of the sandbox by Sesc and Senac streamlines the innovation and risk management of these organizations and establishes controlled environments that drive the validation of new technologies and strategic collaboration, with the aim of enhancing local socio-economic development.
Keywords: Ambiente experimental; Encomendas tecnológicas; Gestão de riscos; Sandbox regulatório; Serviços Sociais Autônomos; Autonomous Social Services; Experimental environment; Regulatory sandbox; Risk management; Technological orders; ACCNPQ::Ciências Sociais Aplicadas::Direito